Ultralow prostate-specific antigen nadir after apalutamide: outcomes in synchronous vrsus metachronous metastatic hormone-sensitive prostate cancer - Wenzel, Mike; Steuber, Thomas; Siech, Carolin; Kriegmair, Maximilian; Hoeh, Benedikt; Tilki, Derya; Merseburger, Axel S.; Chun, Felix K. H.; Mandel, Philipp (European urology open science, 2025)
As an ultralow prostate-specific antigen (PSA) nadir (≤0.02 ng/ml) after apalutamide treatment for metastatic hormone-sensitive prostate cancer (mHSPC) was associated with the best oncological outcomes, the question arises as to whether this holds true for both synchronous and metachronous mHSPC. We addressed this knowledge gap using data from the FRAMCAP (Frankfurt Metastatic Cancer of the Prostate) database. In a cohort of 75 patients with synchronous mHSPC treated with apalutamide, 35% experienced a PSA decline to ≤0.02 ng/ml. Analysis of time to castration-resistant prostate cancer (CRPC) and overall survival (OS) revealed significant differences by PSA nadir category (p < 0.01). In a cohort of 33 patients with metachronous mHSPC treated with apalutamide, 52% experienced a PSA decline to ≤0.02 ng/ml. Analysis of CRPC revealed significant differences by PSA nadir category (p = 0.02). Although there were no significant differences in OS among the PSA nadir categories (p = 0.3), the best numerical OS outcome was observed for PSA ≤0.02 ng/ml. For the overall group of patients achieving PSA ≤0.02 ng/ml, there were no significant difference in time to CRPC and OS between synchronous and metachronous mHSPC. - Patient summary - Apalutamide is a drug for treatment of metastatic prostate cancer that is sensitive to hormone treatment. We found that a decrease in PSA (prostate-specific antigen) to a very low level of ≤0.02 ng/ml after apalutamide treatment can predict good cancer control. This applies to patients with metastasis when they are first diagnosed and to patients who develop metastasis after their diagnosis of prostate cancer. This level of ≤0.02 ng/ml can be used in discussing prognosis and treatment options with these patients.